Oral rehydration solutions in watery diarrhea in children: what’s new? - I. N. Zakharova; I. V. Berezhnaya; A. T. Kamilova; O. V. Dedikova (Медицинский совет, 2020)
Acute infectious diarrhoea is still a topical problem in pediatrics today. Approximately 95% of children under five years of age suffer from acute intestinal infection at least once or several times. Viral infections are the most common cause of acute gastroenteritis with dehydration. A thorough understanding of the mechanisms of dehydration, electrolyte metabolism disorders, and mucosal protection of the intestine has allowed to create modern oral rehydration solutions with a combined mechanism of action. Currently, oral rehydration solutions ORS with reduced osmolarity are recommended due to the latest recommendations of the European Society of Pediatric Gastroenterologists, Hepatologists and Nutriciologists, containing probiotics with targeted anti-inflammatory action. Lactobacilli are the most studied microorganisms and are used either as drugs or as components of functional nutrition. One of the strains of L. reuteri in the metabolic process produces bacteriocin reuterin, which has a powerful anti-inflammatory potential. It is known that the L. reuteri, in addition to standard rehydration therapy, has had an effect on reducing the frequency and severity of diarrhea (by 74% compared to placebo). In subsequent studies, the DSM 17938 strain of L. reuteri was used simultaneously with rehydration solution and zinc, showing a significant reduction in the volume and frequency of watery diarrhoea. The possibility of using a combined preparation containing oral rehydration salts, zinc and probiotic L. reuteri DSM 17938 (Protectis) allows for a more effective elimination of dehydration in young children.